Design and development of image processing algorithms for traffic applications - Abdul Gaffoor Malick Batcha (2013)
Most traffic regulators use surveillance cameras to monitor road traffic patterns, perform post-accident investigation and gather traffic statistics. For statistical data collection, it heavily involves manual counting of vehicles through the surveillance footage which is tedious and unreliable process. With the aid of autonomous traffic analysis software, it improves the process of road traffic data analysis, and it provides more accurate and timely road traffic information.